THE ROLE OF BORROWINGS IN THE DEVELOPMENT OF INTERLINGUAL COMMUNICATION - Nishonova SHaxnoza (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Borrowed words in languages ​​are words that have passed from one language to another due to linguistic contact and have become part of the lexicon of that language. Borrowed words are one of the main ways of enriching the lexicon of the language, and there is no language in the world that has not received any borrowed words.